Duas versões do desejo : Lacan, Deleuze e Guattari - Wendling, Michelle Menezes (2010)
This work focuses on the delimitation of the desire as a lack, in Seminar 7, of Jacques Lacan, and as an excess, in the Anti-Oedipus, of Gilles Deleuze and Félix Guattari. Lacan resumes Freud's criticism to "Love your neighbour as yourself" to discuss some ideas that came to lead what he called the analytical pastoral, focused on promises of happiness and a kind of orthopaedics of the subjects. One of the critical strategies for Lacan is the use of structuralism, which is also one of the focuses of the criticism from the Anti-Oedipus. Deleuze and Guattari oppose the desire as excess to the structured unconscious as language, permeated by a fundamental lack. When approaching the desire we consider that: a) it is impossible to create, or even to say, a concept, as well as to make a clinic without putting them as policy, b) it is impossible to think of concept or clinic without seeing them as responses to certain political issues c) the indifference in politics or philosophy is possible, but not the indifference to politics or philosophy. Thus, we focus on a study of the connections between the Seminar 7 and the Anti-Oedipus and some aspects of the intellectual-political French scene of the second half of the twentieth century that involved the participation of Lacan, Deleuze and Guattari, especially the structuralist "movement". Moreover, we focus on a study of the concept of desire as a lack, from which the coordinates are set from the Other. In the game distanceproximity of the Other, the incest s prohibition is placed as a fundamental for structuring the unconscious as a language. The decoys produced in this game connect themselves to the search of the object as a good that must be found again. But the Supreme Good is a good that has always been forbidden and, as such, a condition of the possibility of desire. The desire as excess was thought from the choice of Deleuze and Guattari for the historical perspective, which results in the defence of the posterity of the law, opposed to the existence of a primordial Law from which would be born the desire. Some implications in the field of ethics were highlight from these definitions of desire. In addition to the fact that Seminar 7 devotes itself to the ethics of psychoanalysis, established as a "not to yield to his desire," as a direct opposition to the analytical pastoral and its attempt to appease the desire, the Anti-Oedipus is also permeated by ethical issues. We mainly take into account the discussion of psychoanalysis as a theory and practice without an alibi and the Anti-Oedipus as a book of non-fascist ethics.